Peningkatan Literasi Statistik melalui Pelatihan Statistical Package for the Social Sciences bagi Mahasiswa Manajemen Bencana - Hayatul Khairul Rahmat; Rahmad Akbar; Dzulhijjah Yetti; Nurbit Nurbit; Yedi Sispurwanto; Harmi Yelmi; Nurkholis Nurkholis (PT Hakhara Akademia Indonesia, 2025)
Statistical literacy is a fundamental competency for Disaster Management students, as disaster-related decision-making relies heavily on the analysis of risk, vulnerability, capacity, and disaster impact data. However, various studies and learning experiences indicate that students still face difficulties in understanding applied statistical concepts and operating data analysis software such as the Statistical Package for the Social Sciences (SPSS). This community service activity aims to improve the statistical literacy of Disaster Management students through structured, practical, and disaster-contextualized SPSS training. The implementation method includes stages of needs analysis, training module design, hands-on practice–based training, and evaluation through pre-tests and post-tests. The results of the activity show a significant improvement in students’ understanding of basic statistical concepts, their ability to process and analyze disaster-related data using SPSS, as well as increased confidence in preparing data-driven scientific reports. This program is expected to contribute to improving the quality of human resources in the field of disaster management by promoting evidence-based decision making.